Ethical decision-making practice among Malaysian consultant quantity surveyors - Hashim, Nor Atikah (2019)
There are many unethical behaviours being practiced in the construction industry that lead to corruption, such as dishonesty, cheating, selfishness and bribery. Even though these issues are common problems in the Malaysian construction industry, there is still a lack of studies in Malaysia on ethical decision-making (EDM), especially in the field of the quantity surveying practice. As stated by Abdul-Rahman (2010), one of the problems is in the area of tendering, where the evaluation process is usually conducted by the quantity surveyor (QS). Understanding how EDM is structured in the context of the consultant quantity surveyor (CQS) practice through the perspective of human resource development (HRD) is vital to help the profession grow and sustain itself. The nature of CQS work involves dealing with construction-related legal and financial matters, such as payments for work done, time delays and extensions, and losses and expenses. The need for CQSs to consult and advise the project team on a daily basis puts them in stressful situations and the task requires an expert in the field to convince the professional teams to follow the conditions of the contract. Past research has shown that self-control is an important factor in ensuring practitioners comply with ethical standards. Thus, this research intends to identify the compliance issues of EDM in the CQS practice and to understand why CQSs comply with EDM in practice. This study addresses the concept of knowledge acquisition and how professionals learn. Situated learning and experiential learning serve as the foundations upon which learning from experience can be analysed and better understood, especially in the area of EDM. The role of self-control is also addressed to identify the importance of EDM in professional practice. Acquiring expertise in EDM is essential for CQSs to perform their duty well and to safeguard the clients’ interest in construction projects. However, how do CQSs learn EDM? How do CQSs practice EDM in professional practice? And why do CQSs comply with EDM in professional practice? The researcher used a qualitative method to investigate EDM knowledge construction among CQSs through knowledge development, situated learning, experiential learning and self-control theory in professional practice to gain an in-depth understanding of the phenomenon. There is a lack of qualitative research on EDM, especially in the area of the quantity surveying practice within the context of the Malaysian construction industry. Therefore, a qualitative research methodology was selected to gain more detailed and valid descriptions of the phenomena studied. This methodology allowed the respondents to discuss personal data more freely and openly in in-depth interviews. The selection of respondents was limited to CQSs who registered with the Board of Quantity Surveyors Malaysia (BQSM) and practiced within the Malaysian construction industry. From the results, the researcher suggests that several attributes give meaning to EDM in the CQS professional practice, including duty of care and safeguarding a good reputation for the company and themselves. As an ethical person, the CQS shows integrity by being responsible, accountable, trailing excellence and exercising self-restraint. They demonstrate the ability to respond to expectations in their professional practice through EDM.